HOW LATVIAN DEVELOPERS LEARN NEW TECHNOLOGIES. A CONCLUSIVE REVIEW AND ANALYSIS OF SURVEY DATA - Arbidāne, Sandra; Silickis, Mārtiņš; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
The goal of research is to give an overview of the skills, tools and informal learning methods used by Latvian software developers and IT students to learn new technologies and compare results with similar international survey conducted by “Stack Overflow”. Furthermore, another author’s survey campaign aimed at IT industry employers to study their opinion about current workforce situation in Latvia’s IT industry’s labour market, and main criteria that are important for hiring new job applicants. This insight research is based on survey, where 8 employers and 52 software developers and students responded on the questions